Off the grid [compact disc, unabridged] - Tracy, P. J. (Tracy, P. J. Monkeewrench novel., 2012)
As Minneapolis homicide detectives Leo Magozzi and Gino Rolseth struggle to link three crimes, they learn that there have been similar murders in other cities around the United States. Piece by piece, evidence accumulates, pointing to a suspect that shocks them to the core, uncovering a motive that puts the entire Midwest on high alert and Monkeewrench in the direct line of fire.